Memahami Komunikasi Verbal dalam Interaksi Manusia - Hamama, Syifa; Nurseha, Muhammad Achid (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
Communication is a key element in people's daily lives. Through communication, ideas, feelings, and information can be conveyed from one individual to another. One of one of the most common and effective forms of communication is verbal communication. Verbal communication involves the use of words, both spoken and written, to convey a message. message. In this article, we will discuss the importance of verbal communication and its role in enhancing human interaction